ANALISIS KELAYAKAN FINANSIAL BUDIDAYA LELE FERMENTASI (BULETASI) DI PETERNAKAN LELE BAPAK TUGIRIN DI DESA SRIMULYO, PIYUNGAN, BANTUL, YOGYAKARTA - Nina Fitrianingsih; Suprih Sudrajat; Wahyu Setya Ratri (JURNAL ILMIAH AGRITAS, 2022)
The purpose of this study was to determine the income and financial feasibility of the fermented catfish farm of Mr. Tugirin, in Srimulyo, Piyungan, Bantul, Yogyakarta through the implementation of financial feasiblity analysis. The method used in this study is a descriptive method with a quantitative approach. Whereas the research techniques used are survey methods. The research area was purposively (intentionally), in which the number of data samples was 3 periods, and each period was 3 months until harvest. The data used in this study are primary and secondary data. The analysis used is for financial feasibility that has been tested using t tests. Based on the study, the fermented catfish farm of Mr. Tugirin, in Srimulyong, Piyungan, Bantul, Yogyakarta has financial value as per B/R ratio > 0 and R/C ratios > 1